(3GdGeWGQs - (3LQGH GdOhdI , CMeO Hf eMeO Hf YdhLI GdSLRj GdHZOGOj, CHh GdYHGSs
(3ChdgG (B:s
(3GYde Cf GdbeQ EPG UGQ eY GdTeS ObjbI HObjbI hgh GdELJeGY agh GdJCSjS s
(3BNQgG (B:s
(3hGdfMhS EPG cGfJ TQbjI jJUd GdchGcH GdZQHjI Od Ydi Gdaje HdG eWQ aGfge eG eKdK dc hGYed Hg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B128s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi s
Keywords: (3Gdadcs